Retained ratio of reinforcement in SAC305 composite solder joints: effect of reinforcement type, processing and reflow cycle. Issue 3 (6th June 2016) - Chen, Guang; Liu, Li; Silberschmidt, Vadim V.; Chan, Y.C.; Liu, Changqing; Wu, Fengshun
Abstract : Purpose: This paper aims to systematically study the effect of reinforcement type, processing methods and reflow cycle on actual retained ratio of foreign reinforcement added in solder joints. Design/methodology/approach: Two kinds of composite solders based on SAC305 (wt.%) alloys with reinforcements of 1 wt.% Ni and 1 wt.% TiC nano-particles were produced using powder metallurgy and mechanical blending method. The morphology of prepared composite solder powder and solder pastes was examined; retained ratios of reinforcement (RRoR) added in solder joints after different reflow cycles were analysed quantitatively using an Inductively Coupled Plasma optical system (ICP-OES Varian-720). The existence forms of reinforcement added in solder alloys during different processing stages were studied using scanning electron microscope, X-ray diffractometry and energy dispersive spectrometry. Findings: The obtained experimental results indicated that the RRoR in composite solder joints decreased with the increase in the number of reflow cycles, but a loss ratio diminished gradually. It was also found that the RRoR which could react with the solder alloy were higher than that of the one that are unable to react with the solder. In addition, compared with mechanical blending, the RRoRs in the composite solders prepared using power metallurgy were relatively pronounced. Originality/value: Present study offer a preliminary understanding on actual content and existence form of reinforcement added in a reflowed solder joint, which would also provide practical implications for choosing reinforcement and adjusting processing parameters in the manufacture of composite solders.